Dampak Dan Upaya Preventif Kasus Illegal Unregulated Unreported (IUU) Fishing Di Laut Indonesia - Andika Andika; Joviento Joviento; M Taufiq Ar Rauf (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Illegal Unregulated Unreported (IUU) fishing is a fishing activity that is illegal, not reported to the authorized fisheries management institution, and a fisheries activity that has not been regulated in existing regulations. The aim of this research is to determine the impacts that occur and efforts to prevent cases of Illegal Unregulated Unreported (IUU) Fishing in Indonesian seas. This research uses a type of qualitative research with a literature study method known as literature review. The impact of the case consists of social, political and environmental impacts. The Government of the Republic of Indonesia can carry out prevention in the form of community empowerment and fishing actors and become a member of the IPOA (International Plan of Action) which was pioneered by FAO in implementing the CCRF (Code of Conduct for Responsible Fisheries).